Application of ICRP recomendations to radioactive waste isolation - Beninson, Dan Jacobo; Lindell, B. (Comisión Nacional de Energía Atómica; Argentina, 1985)
Fil: Beninson, Dan Jacobo Comisión Nacional de Energía Atómica; Argentina